Exploring Intimate Partner Violence in Polynesia: A Scoping Review. (October 2020) - Heard, Emma; Fitzgerald, Lisa; Whittaker, Maxine; Va'ai, Sina; Mutch, Allyson
Intimate partner violence (IPV) is a major, global public health concern with significant impacts, particularly for women, worldwide. There is an immediate need to develop comprehensive understandings of the complex drivers of this multifaceted issue in diverse cultural and social contexts. This scoping review used a systematic approach to gather a broad scope of peer-reviewed, publisher-controlled, and gray literature investigating IPV in Polynesia, a region of the Pacific experiencing high rates of IPV. A total of 181 articles were identified through a comprehensive search that included five cross-disciplinary databases; government, intergovernmental, and nongovernment websites; and consultation with community organizations. Thirty-three articles met the inclusion criteria related to IPV in a Polynesian country or community abroad and were included in this review. Narrative synthesis, which included summarizing and sorting key findings into common themes, was conducted to provide an overview of what is currently known about IPV in Polynesia and Polynesian communities living aboard. Key themes, which arose from the data analysis included: high prevalence of IPV, attitudes supporting IPV, urbanization and migration, traditional protective factors, and formal leadership and laws. The paucity of rigorous literature highlights an immediate need for IPV prevention research and intervention within Polynesian communities. This review includes a discussion of the limitations of this small body of literature and makes recommendations for future research, policy, and program development to include intersectionality in order to deepen understandings and enhance inclusive and meaningful intervention and policy implementation.